Waste copper slag in special concrete: Current research and future applications - Martyna Nieświec; Paweł Niewiadomski; Łukasz Sadowski; Christof Schroefl (Materials & Design)
Self-compacting concrete (SCC) and high-performance concrete (HPC) are examples of special concretes that have been developed as a result of the ongoing evolution of societal needs and the desire for alternatives to traditional concrete. This study investigates the potential of copper slag, a by-product of copper smelting, as a sustainable component for SCC, HPC, and beyond, with a special focus on 3D printable mixtures and high-performance self-compacting concrete (HPSCC). The study highlights current gaps in the literature. Little attention has been paid to potential copper slag’s function as a chemical/mineralogical active component in comparison to a wider application as a filler substitute in traditional cement-based composites. A thorough analysis outlines advantages and disadvantages of using copper slag, including improved strength and durability, lower water and natural material consumption, and environmental benefits. However, there are challenges indeed, including like its glassy particle surface, prolonged setting times, and enhanced risk of bleeding and segregation. Overall, copper slag still is a promising ingredient for high-performance and ecologically friendly concrete solutions because its benefits exceed its disadvantages. Future research should focus on optimizing the replacement of aggregates and binder components in HPSCC and 3D printable concrete to fully harness the material’s potential.